Addressing refugees Issue in Asia through Dialogue, Ethics and Hospitality Drawing Resource from World Christianity: Religion in the Public Sphere - Shakespeare, S. (University of jaffna, 2024)
This paper proposes that religion can play an important role in the public sphere by addressing the refugee Issue. Minorities in Asia especially religious minorities have been the target of rising right wing nationalism. This paper will bring examples from Srilanka, Myanmar and India. The thirty year war in Srilanka brought misery in the lives of the Tamil people. The demonization of the minority did not only happen within the nation but with the help of powerful nations who for their empire building oppressed the minorities at the international level through international bodies through policies. The rising right wing nationalism in India has demonized the religious minorities especially the Muslims and Christians. The recent tribal conflict in Manipur state shows the danger of religious nationalism. Religious nationalism in Asia has been causing harm and violence to the minorities leaving people as refugees and internally displaced. This paper proposes dialogical and ethical nationalism drawing from world Christianity and Tamil hospitality. The proposed dialogical and ethical nationalism will be a global community that places dialogue, ethics and hospitality at the heart of any nation. Dialogism of Russian scholar Mikhail Bakhtin will be discussed as an alternative to the existing nationalisms. Quoting the example from Mizoram in India is relevant: Mizoram not only welcomed refugees from Myanmar against the popular nationalism, the state also played a very important role in addressing the needs of Manipur people when they fled in thousands during the ethnic violence. World Christianity being dialogic accepts differences and has the capacity to hold different communities together. Resources from world Christianity can be helpful to address the refugee crises.
Keywords: Nationalism; World Christianity; Refugees; Dialogue; Ethics and hospitality